2021
DOI: 10.1073/pnas.2016950118
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cell-derived epithelium misidentified as brain microvascular endothelium requires ETS factors to acquire vascular fate

Abstract: Cells derived from pluripotent sources in vitro must resemble those found in vivo as closely as possible at both transcriptional and functional levels in order to be a useful tool for studying diseases and developing therapeutics. Recently, differentiation of human pluripotent stem cells (hPSCs) into brain microvascular endothelial cells (ECs) with blood–brain barrier (BBB)-like properties has been reported. These cells have since been used as a robust in vitro BBB model for drug delivery and mechanistic under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
152
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(178 citation statements)
references
References 69 publications
14
152
1
Order By: Relevance
“…Before a functional hPSC-derived vascular BBB model can be developed, stable hPSC-derived vascular ECs must be generated. In a recent study (Lu et al, 2021), our group demonstrated that a vascular fate can be induced in iBMECs through introduction of certain EC-specific ETS TFs (ETV2, ERG, and FLI1). These reprogrammed cells (rECs) harbor an EC transcriptomic profile, retaining a PECAM1 + CDH5 + KDR + EC immunophenotype during passaging and expansion.…”
Section: Possible Means For Induction Of Vascular Bbb Phenotype In Hpmentioning
confidence: 99%
“…Before a functional hPSC-derived vascular BBB model can be developed, stable hPSC-derived vascular ECs must be generated. In a recent study (Lu et al, 2021), our group demonstrated that a vascular fate can be induced in iBMECs through introduction of certain EC-specific ETS TFs (ETV2, ERG, and FLI1). These reprogrammed cells (rECs) harbor an EC transcriptomic profile, retaining a PECAM1 + CDH5 + KDR + EC immunophenotype during passaging and expansion.…”
Section: Possible Means For Induction Of Vascular Bbb Phenotype In Hpmentioning
confidence: 99%
“…iPSC-EC models have been noted to exhibit morphological and physiological characteristics closest to in vivo characteristics, with comparable barrier integrity, protein and transporter expression and barrier permeability. It should be highlighted that pluripotent-derived endothelial cells should be confirmed as bona fide endothelial cells before use in in vitro model systems [49]. The inclusion of multiple cell types, including ECs, astrocytes, pericytes and neurons, improved barrier integrity, and the conditioning of these cells in brain-specific media (i.e., astrocyte and neuron) further strengthened the barrier.…”
Section: Discussionmentioning
confidence: 99%
“…hPSCs are an attractive model system to complement in vivo animal studies because they (i) are human, (ii) permit investigation of developmental processes in contrast to primary or immortalized cells, (iii) are highly scalable, (iv) can be derived from patients to facilitate disease modeling and autologous coculture systems, and (v) are genetically tractable. While widely used hPSC-based BBB models are useful for measuring molecular permeabilities and have been employed to understand genetic contributions to barrier dysfunction (Vatine et al, 2016(Vatine et al, , 2019Lim et al, 2017), they have not been shown to proceed through a definitive endothelial progenitor intermediate (Lippmann et al, 2012;Lu et al, 2021) and express epithelial-associated genes (Qian et al, 2017;Delsing et al, 2018;Vatine et al, 2019;Lu et al, 2021). Thus, new models with developmentally relevant differentiation trajectories and definitive endothelial phenotype are needed for improved understanding of developmental mechanisms.…”
Section: Discussionmentioning
confidence: 99%